2021
DOI: 10.3892/etm.2021.10411
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating field stimulation promotes recovery from spinal cord injury in rats by regulating the differentiation of endogenous neural stem cells

Abstract: The mammalian spinal cord (SC) has a limited selfrepair capacity and exogenous treatments are yet to produce substantial functional recovery following SC injury (SCI). The SC contains endogenous neural stem cells (NSCs) with multi-lineage differentiation potential and it may be possible to restore function via interventions that promote NSC differentiation following SCI. Oscillating field stimulation (OFS) has been reported to regulate the Wnt signaling pathway, a known modulator of NSC differentiation. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“… 79 In another study, hematoxylin and eosin staining showed that electrical stimulation reduced the number of infiltrating inflammatory cells in the lesion site compared with controls. 81 Detection of calpain, a protease that triggers cell death post-injury, and a DNA detection method for apoptotic cells both showed reduced levels in ES-treated rats after spinal cord injury. 75…”
Section: Assessing the Effects Of Electrical Stimulation Treatment On...mentioning
confidence: 99%
“… 79 In another study, hematoxylin and eosin staining showed that electrical stimulation reduced the number of infiltrating inflammatory cells in the lesion site compared with controls. 81 Detection of calpain, a protease that triggers cell death post-injury, and a DNA detection method for apoptotic cells both showed reduced levels in ES-treated rats after spinal cord injury. 75…”
Section: Assessing the Effects Of Electrical Stimulation Treatment On...mentioning
confidence: 99%